A comparison of surface complexation models for quantitative description of acidic properties of fumed silica - Vlasova, N. N. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2008)
The possibilities of different surface complexation models to describe quantitatively acidic properties of fumed silica have been studied. The dissociation constants of silanol groups of amorphous silica have been calculated using potentiometric titration data, different electrostatic models, and GRFIT program package. It has been shown that basic Stern model can sufficiently characterize protolitic properties of silica, their dependence on ionic strength and pH, operating with reasonable set of parameters which have certain physical sense.